2017
DOI: 10.1016/j.jped.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Association between weather seasonality and blood parameters in riverine populations of the Brazilian Amazon

Abstract: Hematological parameters of the red cell series and blood iron homeostasis had seasonal variation, which coincided with the dry season in the region, in which an increase in atmospheric pollutants derived from fires is observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
3
0
2
Order By: Relevance
“…They concluded that age and seasonality have an impact on mean values for hematological parameter intervals in the first five years of life (Okebe et al, 2016). Also, in a cross-sectional study of 120 school-aged children and teens, the hematocrit was found to reduce significantly during the rainy season while red cell series and blood iron homeostasis had seasonal variation (Rodrigues, Ignotti, & Hacon, 2017). Moreover, in a study of 27,478 children aged 7-17, white blood cell counts were statistically significantly higher in the winter and spring than in the summer and autumn (p ≤ 0.05).…”
Section: Discussionmentioning
confidence: 91%
“…They concluded that age and seasonality have an impact on mean values for hematological parameter intervals in the first five years of life (Okebe et al, 2016). Also, in a cross-sectional study of 120 school-aged children and teens, the hematocrit was found to reduce significantly during the rainy season while red cell series and blood iron homeostasis had seasonal variation (Rodrigues, Ignotti, & Hacon, 2017). Moreover, in a study of 27,478 children aged 7-17, white blood cell counts were statistically significantly higher in the winter and spring than in the summer and autumn (p ≤ 0.05).…”
Section: Discussionmentioning
confidence: 91%
“…Remarkably, the iron status of the adolescent girls in this study differed with the season, with the highest prevalence of ID observed in the wet season in the three saline regions. A Brazilian study showed the mean serum ferritin concentrations of riverine populations were higher in the dry season than in the rainy season 52 . One reason contributing to the increasing levels of ID during the wet season may be the mixing of surface water and groundwater during the rainy season, which lowers the overall iron content of the mixed water 53 .…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, as frequências de anemia no Brasil apresentam grandes variações dependendo da região estudada (comunidade, cidade e/ou estado), local da coleta (Unidade Básica de Saúde ou em creches/escolas), e a idade do grupo estudado [5][6][7][8][9][10][11][12][13] . Pois, diversos fatores podem influenciar o desfecho estudado.…”
Section: Discussionunclassified
“…Na literatura, os fatores que associam com a anemia estão envolvidos com as características socioeconômicas, maternas, de aleitamento materno, e fatores individuais das crianças [5][6][7][8][9][10][11][12][13] . Podendo destacar a menor renda, o maior número de moradores 5 , maior número de filhos 5,7 , amamentação não exclusiva 12 , menor idade materna 9 , menor idade da criança e o estado nutricional 11,12 .…”
Section: Introductionunclassified